Upaya Menjaga Kesehatan Ginjal Dengan Pemeriksaan eGFR dan Serum Kreatinin Sejak Awal pada Populasi Usia Produktif di Kelurahan Grogol - Drew, Clement; Santoso, Alexander Halim; Gunaidi, Farell Christian; Zhalila, Zhillan; Pranata, Catherine Christiana (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Chronic kidney disease (CKD) is a metabolic disorder that is increasingly prevalent among the productive-age population and can significantly impair quality of life, particularly due to its progressive nature and often asymptomatic presentation in the early stages. Routine assessments of kidney function—such as estimated glomerular filtration rate (eGFR) and serum creatinine levels—are essential for the early detection of kidney impairment. The Community Service Program (PKM) conducted in Grogol Village aimed to raise public awareness regarding the importance of early screening for kidney dysfunction. Among the 71 participants involved in the activity, 9 individuals (12.68%) had elevated serum creatinine levels, 4 individuals (5.63%) showed evidence of stage 3a kidney function decline, and 31 individuals (43.66%) were identified with stage 2 kidney function decline. Only 36 participants (50.7%) had normal kidney function. These results underscore the necessity of early detection efforts to prevent the progression of CKD and to promote sustained public awareness on the importance of maintaining kidney and metabolic health. Keywords: Chronic Kidney Disease, Creatinine, eGFR, Early Detection, Productive Age